Analisis Pengaruh Elemen Gamifikasi pada Aplikasi Pembelajaran Terhadap Motivasi Belajar Siswa SMA - Pahlevi, Reza; Mulyati, Sri (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The advancement of technology in the information era has significantly impacted the field of education, enabling more interactive and innovative learning methods. One such emerging innovation is the application of gamification technology in education, which aims to enhance students' learning motivation by applying game principles within non-game contexts. This study examines the impact of various gamification elements, including scores, missions, levels, achievements, feedback, avatars, and leaderboards, on students learning motivation. Using the multiple linear regression analysis method., the research found that all these elements significantly influence student motivation, with the leaderboard showing the highest impact. The leaderboard, which positions or ranks students based on performance, has proven to be a particularly strong motivator, with a regression coefficient of 0.234, surpassing other gamification elements. These findings provide practical guidance for educators and educational app developers to prioritize the leaderboard element in the design of gamified learning systems. This study’s results are expected to support more effective and interactive learning strategies, ultimately increasing student engagement and learning outcomes.